Preparation of iron oxide–coated aramid fibres for improving the mechanical performance and flame retardancy of multi jet fusion–printed polyamide 12 composites - Hou, Yanbei (2023)
Multi jet fusion (MJF), a powder-based additive manufacturing technology, is suitable for fabricating fibre-reinforced polymer composites. However, the types of reinforcement fibres applied in MJF are limited due to the incompatibility between the fibres and polymer. Herein, a simple and cost-effective surface modification method for Fe3O4-coated aramid fibres (Fe3O4@AF hybrids) is proposed to fabricate polyamide 12 (PA12) composites by MJF. The optimal fibre content for Fe3O4@AF/PA12 composites is 6 wt%, which resulted in 10.83% and 16.05% higher ultimate tensile strength and Young’s modulus, respectively, compared with AF/PA12. The addition of Fe3O4@AF hybrids also improved the flame retardancy of AF/PA12 by reducing the peak heat release rate (PHRR) and postponing the temperature at PHRR. This practical surface modification method can be potentially applied to other reinforcement fibres for fabricating functional polymer composites by other powder-based manufacturing technologies.